5-Azacytidine partially restores CD20 expression in follicular lymphoma that lost CD20 expression after rituximab treatment: a case report. (December 2016) - Tsutsumi, Yutaka; Ohigashi, Hiroyuki; Ito, Shinichi; Shiratori, Souichi; Teshima, Takanori
Abstract Background The loss of CD20 protein expression after a rituximab-containing regimen is one of the resistance mechanisms in non-Hodgkin's lymphoma. Recently, it was reported that 5-azacitidine administration upregulates the expression of CD20 in CD20-negative B-cell acute lymphoblastic leukemia. Here we report a similar upregulation in a patient with follicular lymphoma who was treated with 5-azacitidine against secondary myelodysplastic syndrome. Case presentation A 69-year-old Japanese woman with follicular lymphoma with treatment-related myelodysplastic syndrome was negative for the CD20 antibody at the time of her relapse. After treatment of 5-azacytidine for her myelodysplastic syndrome, CD20 expression was upregulated in the follicular lymphoma cells in her peripheral blood. We also observed follicular lymphoma cell stimulation in her peripheral blood due to 5-azacytidine. Conclusions Although partial, CD20 expression was upregulated after treatment with 5-azacitidine. However, CD20 expression was not re-upregulated after a second administration of 5-azacitidine and we also observed the risk of lymphoma cell stimulation due to 5-azacitidine.